Analysis of quality of life in elderly practitioners of physical activity and relationship with risk of falls. - Pires-Oliveira, Deise Aparecida de Almeida; Gil, André Wilson Oliveira; Oliveira, Laís Campos de; Bento, Felipe Micheletti; Mendes, Camila Silva Tomioto; Santos, João Paulo Manfré dos (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Old age brings several factors that changes the physiological system, which results in loss of functionality in the elderly. Falls are a leading cause of death in this population or activity restrictions, social isolation, decline in health and increased risk of institutionalization. The quality of life in old age is a major challenge, it is necessary for improvement in all aspects of daily. Analyze physical exercise on quality of life of older physically active drives to see how exercise influences the improvement of the basic aspects to a healthier life, referring to physical and mental aspects of the elderly, prevention of the consequences arising from the process natural aging, such as falls. Objective: The aim of this study is to analyze quality of life in elderly practitioners of physical activity and relationship with risk of falls. Method: 84 seniors, recruited from the community of Londrina PR, physical activity practitioners, aged over 60 years who roam with or without assistive device, of both gender, composed the sample. The evaluation was through structured questionnaires that focused on socioeconomic - demographic questionnaire falls which was used the Timed Up and Go (TUGT), analysis of quality of life (SF-36) and analysis of the risk of falls. Results: In relationship the anthropometrics characteristics of elderly subjects analyzed, the same presentation mean age 68 years, weight 63.5 kg, height 1.52, and body mass index 27.10. Was regarding correlation between TUGT and falls in the last year (P=0,048) e correlation between TUGT and Physicals Components of SF-36 (P=0,001), and was regarding that elderly with better scores in TUGT were better scores of Physical Components of SF-36 (P=0,003). Conclusion: The quality of life is directly linked to the physical condition of the elderly, elderly practicing physical exercises have a better quality of life and less prone to falls.